THE IMPLEMENTATION OF CEDAW PRINCIPLES ON REDUCING GENDER-BASED VIOLENCE DURING THE COVID-19 PANDEMIC - Afandi Sitamala; Ferina Ardhi C; Ahmad Lanang C (Journal of Law and Policy Transformation, 2022)
This study aims to identify the principles of CEDAW and analyze them to determine the effectiveness of these principles in reducing gender-based violence during the outbreak. The study was carried out using normative legal research methods that included a conceptual and statutory approach. A literature research will be used to acquire legal materials, and the legal materials will be assessed using CEDAW principles. The study's findings reveal that there are three foundational principles of the CEDAW these are non-discrimination, substantive equality, and state obligation. The principles are effective on plummeting gender-based violence in pandemic outbreak. The full application of the CEDAW principles remains a significant challenge.